Comprehensive analysis of life quality of patients with vitiligo in Romania: insights from a multivariate approach - Fekete, László; Bacârea, Vladimir; Fekete, Gyula László; Fekete, Júlia Edit; Kovács, Béla (Frontiers in Medicine, 2025)
BackgroundVitiligo is a rare skin disorder affecting approximately 2% of the world’s population with significant impact on body image and subsequent psychosocial involvement in terms of self-esteem and quality of life. Our study focused on assessing these psychosocial aspects in Romanian vitiligo patients.MethodsAssessment of self-esteem and quality of life were evaluated by self-reported completion of the Rosenberg self-esteem and Dermatology Life Quality Index validated questionnaires. Sociodemographic data were also collected from the 114 respondents, including age, gender, residence, marital status, level of education and debut of vitiligo. Besides classical statistical evaluation, dimensionality reduction analysis techniques, such as principal component analysis and multiple correspondence analysis were employed to investigate in complexity the impact of various factors on the quality of life and self-esteem of patients with vitiligo.ResultsOur findings suggest that age, marital status and disease duration were amongst the most important factors that affects the psychosocial well-being of patients with vitiligo. Elderly, married patients with long-established vitiligo scored better on the quality-of-life outcomes and higher on the self-esteem questionnaire compared to their younger, single and recently diagnosed peers with vitiligo.ConclusionOur findings highlight the significant influence of sociodemographic factors on self-esteem and quality of life in vitiligo patients, emphasizing the need for further research and personalized support to address the psychosocial impact of the condition.